Social interactions in bacteria mediated by bacteriocins and horizontal gene transfer - Thomas, JL (2023)
Bacteria are highly social organisms that frequently engage in cooperative and competitive interactions to successfully survive and reproduce. Examples include cell-to-cell communication, nutrient scavenging, and chemical warfare. However, the vast majority of our understanding of bacterial sociality has come from the laboratory strains of a small number of gram-negative social evolution model organisms, such as Pseudomonas spp. and Escherichia coli. In my thesis, I aim to expand our understanding of bacterial sociality in natural populations and further across the bacterial tree of life. I do this using two different approaches. Firstly, I use laboratory experiments and sequence analysis to study the evolution and ecology of bacteriocin-mediated competition in natural S. aureus populations, sampled as part of a carriage study on human nasal passages. Theory and laboratory experiments to date have provided extensive evidence that bacteriocin production plays a key role in determining the competitive dynamics of bacterial strains, however evidence from natural populations to support this hypothesis is lacking. I find that inhibitory strains were associated with the propensity to displace competing strains from the nasal cavity, which occurs despite inhibitory activity not being displayed by the majority of strains and targeting interspecific over intraspecific competitors. I also provide evidence for the genetic underpinnings of bacteriocin activity, by identifying five bacteriocin gene clusters associated with inhibition. Secondly, I use a comparative approach to study the role of horizontal gene transfer in stabilising cooperation across bacteria. Bacterial cooperation is typically mediated by the secretion of extracellular public goods, which are costly molecules that provide a fitness benefit to neighbouring cells. Cooperation can be destabilised by the invasion of selfish ‘cheats’ that reap the benefit of public good production without paying a cost. It is widely accepted that horizontal gene transfer, especially via plasmids, can allow cooperators to ‘re-infect’ cheats with the gene for a cooperative trait, thus stabilising cooperation. Although theoretical and experimental studies have provided evidence to support this hypothesis, a comprehensive genomic study that controls for phylogenetic non-independence across species remains to be conducted. The results from our analysis of plasmid genes from 51 diverse bacterial species do not support the cooperation hypothesis across bacteria and are instead supportive of environmental variability as a determining factor in the relationship between horizontal gene transfer and extracellular proteins. Taken together, this thesis provides a body of work that emphasises the importance of testing predictions from theoretical and laboratory experiments in natural populations, and across diverse species.